CREATION OF MAN IN ISLAM AND HINDUISM: AN INTELLECTUAL ENCOUNTER - Islam, Arshad (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2025)
This study examines the similarities and differences in ontological views of the creation process as described in Islam and Hinduism. The Islamic view is based on the Qur’ān and Ḥadīth, expounded in the commentaries and auxiliary works of the Islamic scholars, and the Hindu view is rooted in the oldest Vedic scriptures, particularly the Rig Veda. The Qur’ān reaffirms the Judaic account of the creation of Adam as the primordial human, who was established as a vicegerent in the earth. It repeatedly iterates the Quranic theme of the incredible fine-tuning of creation being a cause for reflection on the meaning and significance of the universe, rather than being a random or idle occurrence. The Qur’ān declares that human beings have a uniquely privileged role in the destiny of the Universe. They are not an irrevocably fallen creature, as believed by Christians. The Islamic paradigm is fundamentally centered on the divine mandate of humans to worship their Creator, whereby they may return to their Paradisal homeland; exhibiting some similarities and differences, the Vedic theory of Creation posits that the universe is of immense age, and that humans have descended (devolved) from a higher state of consciousness to their current impasse. It must seek to re-ascend to their former status and unity with the transcendent Absolute. The study then zooms out to offer a comparative analysis of general Islamic views of Hinduism and some modern Hindu views of Islam.